2008
DOI: 10.1002/elan.200804160
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pulse Voltammetric Determination of Uric Acid on Carbon‐Coated Iron Nanoparticle Modified Glassy Carbon Electrodes

Abstract: A carbon-coated iron nanoparticles (CIN, a new style fullerence related nanomaterial) modified glassy carbon electrode (CIN/GCE) has been developed for the determination of uric acid (UA). Electrochemical behaviors of UA on CIN/GCE were explored by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). It was found that the voltammetric response of UA on CIN/GC was enhanced dramatically because of the strong accumulation effect of CIN and the large working area of the CIN/GC electrode. The parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Electrochemical studies of UA were mainly concentrated on the modified electrodes. In this manner, the modification of glassy carbon (GC) with covalently linked poly(vinyl alcohol) (Li and Lin, 2006), ribo nucleic acid (RNA) (Kang and Lin, 2006), poly(acrylic acid)-multiwalled carbon nanotube composite (Liu et al, 2007) and carbon coated iron nanoparticles (Wang et al, 2008) have been achieved and their electroanalytical performances were tested in the determination of UA.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical studies of UA were mainly concentrated on the modified electrodes. In this manner, the modification of glassy carbon (GC) with covalently linked poly(vinyl alcohol) (Li and Lin, 2006), ribo nucleic acid (RNA) (Kang and Lin, 2006), poly(acrylic acid)-multiwalled carbon nanotube composite (Liu et al, 2007) and carbon coated iron nanoparticles (Wang et al, 2008) have been achieved and their electroanalytical performances were tested in the determination of UA.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of abnormal UA levels is a sign of gout, hyperuricemia or LeschNyhan syndrome. Therefore, simple, fast and sensitive methods are highly required for the quantification of this bioanalyte 1.…”
Section: Introductionmentioning
confidence: 99%
“…All these slope values of E p versus pH in this paper were approximately close to the theoretical value of À57.6 mV pH À1 at 18 8C for a reversible proton-coupled single electron transfer. The slope of the linear dependences described by equation showed that the electron transfer was accompanied by the transfer of an equal number of protons [25]. In the range of pH 0.5À3.0, i p reached its maximum value at pH 1.0.…”
Section: Effect Of Phmentioning
confidence: 98%
“…Magnetic carbon-coated nickel nanoparticles were prepared by the modified Alternating Current (AC) arc discharge method [24,25]. CNN were purified before use.…”
Section: Preparation Of Cnn/gcementioning
confidence: 99%
See 1 more Smart Citation